Pilot scale test of wet dust removal by high gravity intensification technology in fertilizer plant. Issue 6 (December 2021) - Qi, Guisheng; Cheng, Shangyuan; Liu, Youzhi; Guo, Qiang
Abstract: Industrial dust can cause serious harm to the environment and human body. High gravity wet dust removal is a new type of high-efficiency dust removal technology, with the advantages of high dust removal efficiency, low economic cost, convenient operation and maintenance. In this work, a cross-flow rotating packed bed was used as the wet dust removal equipment, and a pilot scale dust removal experiment platform was built at the production site of the enterprise. The dust removal effect of high gravity wet dust removal technology on granulation waste gas in actual production was also studied. The second compound fertilizer plant of TianJi Group emitted dust-containing exhaust gas with a dust content of about 2500 mg/m 3 during the production process. Different key parameters including high gravity factor, liquid flow rate and liquid circulation time were investigated on dust removal efficiency and fractional efficiency, and the mechanism of high gravity wet dust removal was analyzed. The obtained results suggested that under the conditions of gas flow rate of 400 m 3 /h, liquid flow rate of 0.5 m 3 /h and high gravity factor of 205.61, the dust removal rate was as high as 99.88% with an outlet concentration of less than 10 mg/Nm 3 . Under three hours of clean water absorption cycle, the dust concentration after purification could still be reduced to less than 10 mg/Nm 3, and the dust removal efficiency could reach more than 99%. The relationship between the fractional efficiency of the cross-flow rotating packed bed and the dust particle size was nonlinearly fitted, which showed a good fit. High gravity wet dust removal technology increased the inertial force of particles in the gas through rotation, while atomizing the liquid into a micro liquid. The scales of the two were matched, and the inertial collision was effectively enhanced to improve the dust capture effect. Therefore, high gravity wet dust removal technology can effectively control industrial dust emissions and has a strong potential for industrial applications. Graphical Abstract: Industrial dust can cause serious harm to the environment and human body. Distinct from laboratory simulation of dusty gas, dusty gas in industrial production is more complex and diverse. Different from the traditional scrubbing dust-containing gas technology, the high gravity technology adopted in this study increased the inertial force of particles in the gas through rotation, while atomizing the liquid into a micro liquid. The scales of the two were matched, and the inertial collision was effectively enhanced to improve the dust capture effect. Aiming at the high concentration dust-containing exhaust gas in the actual chemical production, this work carried out the field side-line capture performance research, established the test device and process, improved the capture effect by optimizing the process and operating conditions, and investigated the adaptability of the high gravity wet dust removal technology in the actual production. Under the conditions of gas flow rate of 400 m 3 /h, liquid flow rate of 0.5 m 3 /h and high gravity factor of 205.61, the dust removal rate was as high as 99.88%, and the outlet concentration was less than 10 mg/Nm 3 . Therefore, high gravity wet dust removal technology can effectively control the discharge of industrial dust and has a strong industrial application potential. ga1